Analisis Faktor-faktor yang Mempengaruhi Pembiayaan Syariah pada Sektor Manufaktur di Indonesia NESIA - Heri Sudarsono; Muhammad Hafidz Prasetyo (Banque Syar'i : Jurnal llmiah Perbankan Syariah, 2021)
This study aims to analyze the factors that influence Islamic bank financing in the manufacturing sector (manufacturing industry). Then the internal factors consist of CAR, DPK, NPF, FDR, ROA, BOPO. While the external factors consist of INFLATION and BI_RATE. This research uses ARDL regression analysis technique. The data used in this study are data per month from 2015-2019. And the data obtained comes from reports from the Financial Services Authority (OJK), the Central Bureau of Statistics (BPS), as well as reports from Bank Indonesia (BI). The object of this research is Islamic Commercial Banks in Indonesia. The method of analysis used in this study is regression with the Autoregressive Distributed Lag (ARDL) model. The ARDL model was chosen because by using the ARDL method, it was able to see the influence of the Y variable. The data processing used Eviews 10. From the data processing, it was found that the variables CAR, FDR, and INF did not significantly influence the manufacturing sector. And the variables of DPK, NPF, ROA, BI_RATE, and BOPO have a significant effect on the manufacturing sector. The main contribution in this study is to identify and examine Islamic bank financing to the manufacturing sector in depth.